Representation of the Consumer Society in V. O. Pelevinˋs Novels of the 21st Century - Biriukova, Ekaterina Vadimovna; Larina, Nadezhda Albertovna (KnE Social Sciences, 2021)
This article is devoted to the study of consumer society reflection in V.O. Pelevin‘s works published in the twenty-first century. There is an attempt to determine the main features of the consumer society to which the characters belong: dominance of focus toward to the satisfaction of private needs, the acquisition of material wealth as a means of achieving prosperity and happiness, the quality of consumed products (goods, services, etc.) determines the status of the consumer in society. V.O. Pelevin defines and ridicules capitalist culture using sarcasm and grotesque, demonstrating the image of consumer society exclusively in negative connotations. V.O. Pelevin reconstructs modern society, endowing it with the features of the world we are accustomed to, but absurdly creating his world of sellers and consumers included in a repeating cycle and changing roles depending on status within the framework of artistic reality. Aimed at revealing the author’s attitude to the consumer society and the novel characters’ attitudes to the object of study, selective analysis of a work fragments demonstrates the gradual inclusion of characters in the consumption culture and a deeper study of the phenomenon by the author. The article considers the consumer society reconstruction in the art world of the following works by V.O. Pelevin: novels Generation P, The Werewolf’s Holy Book, Svyashennaya kniga oborotnya, Empire V, Secret Views of the Fuji Mount, [Sekretnye vidi na goru Fuji], and a story Wind search record [Zapis‘ o poiske vetra]. Such a selective analysis reflects the transformation (which, depending on the point of view, can be called both evolution and degradation) of the consumer culture image and the position of the author may be determined. Keywords: consumer society, postmodernism, V.O. Pelevin, novels